Rheumatoid Arthritis – Non Biologic Treatment and Small Molecules 2018
DOI: 10.1136/annrheumdis-2018-eular.5524
|View full text |Cite
|
Sign up to set email alerts
|

AB0497 Effectiveness, tolerability, and safety of tofacitinib in rheumatoid arthritis: a retrospective analysis of real-world data from the st. gallen and aarau cohort

Abstract: BackgroundTofacitinib is an oral JAK inhibitor indicated for the treatment of RA. Efficacy and safety of tofacitinib have been shown in several randomised clinical studies.ObjectivesThe study presented here aimed to assess the clinical tolerability and effectiveness of tofacitinib among patients with RA in real life.MethodsConsecutive patients between June 2013 and April 2017 with RA who fulfilled the American College of Rheumatology/EULAR 2010 criteria were analysed in a prospectively designed analysis of ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The percentage of patients in our study who discontinued TOFA due to adverse events was 9.3% (46/493), which is similar to that reported in most of the literature (3.2%–9.6%) 10 31–35. However, some studies have shown a higher percentage of discontinuation due to adverse events 36 37. For example, Pope et al in 2019, in a long-term extended study found 25.7% of patients discontinued TOFA due to any adverse events and 17.8% discontinuation due to drug-related adverse events 37…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The percentage of patients in our study who discontinued TOFA due to adverse events was 9.3% (46/493), which is similar to that reported in most of the literature (3.2%–9.6%) 10 31–35. However, some studies have shown a higher percentage of discontinuation due to adverse events 36 37. For example, Pope et al in 2019, in a long-term extended study found 25.7% of patients discontinued TOFA due to any adverse events and 17.8% discontinuation due to drug-related adverse events 37…”
Section: Discussionsupporting
confidence: 86%
“… 10 31–35 However, some studies have shown a higher percentage of discontinuation due to adverse events. 36 37 For example, Pope et al in 2019, in a long-term extended study found 25.7% of patients discontinued TOFA due to any adverse events and 17.8% discontinuation due to drug-related adverse events. 37 …”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study of patients using data from the Commercial Claims and Encounters database in the US reported similar efficacy rates at 1-year between tofacitinib and non-TNF biologics [22] An observational Japanese study reported 60% of patients achieved ≥50% improvement in clinical disease activity index (CDAI), with remission rates higher in biologic-naïve patients [23]. The Swiss Clinical Quality Management registry (SCQM) also reported high rates of low disease activity and remission [24]. Crude drug retention rates were similar for tofacitinib as other biologics, with a lower risk of drug discontinuation compared to TNFi [25].…”
Section: The Jak Inhibitors On the Marketmentioning
confidence: 99%